Bacteriological diagnosis of osteoarticular infections caused by Kingella kingae; a narrative review - De Marco, Giacomo; Vazquez, Oscar; Paris, Elio; Cochard, Blaise; Steiger, Christina; Dayer, Romain; Ceroni, Dimitri (Frontiers in Pediatrics, 2025)
In recent years, advancements in modern laboratory diagnostics have identified Kingella kingae (K. kingae) as the major cause of osteoarticular infections in early childhood. The introduction of novel diagnostic methods has ushered in a new era, transitioning from underrated infections to recognizing K. kingae as the primary etiology of skeletal system infections in children. This article provides a new perspective on K. kingae, exploring innovative diagnostic methods that have improved and will continue to transform the management of these infections.